Passalozetes africanus Grandjean 1932 - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 263, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444

Passalozetes africanus Grandjean, 1932 Material – One specimen in Kalecik, N 40° 06′ 44.50′′, E 33° 25′ 43.30′′, alt. = 732 m, 20 July 2018, soil with litter in vineyard. Previous record in Turkey – Erzurum (Ayyildiz 1988). Global distribution – Palaearctic. Ecology – Dry meadow soil.
Keywords: Passalozetes; Arthropoda; Passalozetes africanus; Passalozetidae; Arachnida; Animalia; Biodiversity; Sarcoptiformes; Taxonomy; 2. Zero hunger; 15. Life on land